HIV-related risky practices among Brazilian young men, 2007 - Célia Landmann Szwarcwald; Carla Lourenço Tavares de Andrade; Ana Roberta Pati Pascom; Erika Fazito; Gerson Fernando Mendes Pereira; Isaque Terra da Penha (Cadernos de Saúde Pública)
Behavioral surveillance surveys have been carried among military conscripts, in Brazil, since 1996. This paper presents the results of the 2007 survey and compares actual findings with those obtained in previous studies carried out in the period 1999-2002. The conscripts were selected with a two stage sampling stratified by geographical region. The study included a self-reported questionnaire and blood collection for HIV and syphilis testing. Data from 35,432 conscripts aged 17-20 years old were analyzed. The findings show a reduction in regular condom use, with fixed and casual partners, mainly among those with poor educational level. The proportion of conscripts that have sex with other men was maintained (3.2%), but the index of risky sexual behavioral showed worsening results in this group. Also, the HIV prevalence rate increased from 9 to 11.3 per 10,000 in 2007, though the increase was not statistically significant. In conclusion, the evidences found in this paper indicate the need of reformulate policy among young adults.